2003
DOI: 10.1111/j.1349-7006.2003.tb01481.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological evaluation of CTL precursor‐oriented vaccines for advanced lung cancer patients

Abstract: Recent clinical trials of peptide vaccine for cancer patients have rarely resulted in tumor regression. One of the reasons for this failure could be an insufficient induction of anti-tumor responses in these regimens, in which peptide-specific memory cytotoxic T lymphocytes (CTLs) were not measured prior to vaccination. We investigated in this study whether pre-vaccination measurement of peptide-specific CTLs can provide any advantages in lung cancer patients receiving peptide vaccination with regard to safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 26 publications
2
67
0
Order By: Relevance
“…This indicates that the elicitation of IgG reactive to administered peptides is not limited to the UBE2V 43-51 peptide. In addition, we found that vaccine-induced, peptide-specific IgG tended to detectable in advanced lung cancer patients with a long progression-free survival (23). Although many clinical trials of peptide-based immunotherapy have been conducted to induce CD8 ϩ T cell-mediated tumor regression, no apparent correlation has been observed between in vivo tumor regression and the induction of peptide-specific CTLs in the periphery (3,24).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This indicates that the elicitation of IgG reactive to administered peptides is not limited to the UBE2V 43-51 peptide. In addition, we found that vaccine-induced, peptide-specific IgG tended to detectable in advanced lung cancer patients with a long progression-free survival (23). Although many clinical trials of peptide-based immunotherapy have been conducted to induce CD8 ϩ T cell-mediated tumor regression, no apparent correlation has been observed between in vivo tumor regression and the induction of peptide-specific CTLs in the periphery (3,24).…”
Section: Discussionmentioning
confidence: 77%
“…This means that the dramatic induction of IgG reactive to administered peptides is not limited to the present case. In addition, peptide vaccination resulted in the induction of IgG reactive to several tumor peptides other than the UBE2V 43-51 peptide (22,23). This indicates that the elicitation of IgG reactive to administered peptides is not limited to the UBE2V 43-51 peptide.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We previously reported that IgG reactive against CTL epitope peptides was often detected in the prevaccination sera of cancer patients and also in the sera of HDs, and there was no obvious HLA-class I-A restriction involved (Ohkouchi et al, 2002;Kawamoto et al, 2003;Mine et al, 2003;Noguchi et al, 2003;Sato et al, 2003). Further, some CTL-directed peptides have shown the ability to elicit both cellular and humoral immune responses in vivo in phase I clinical studies, and levels of antipeptide IgG in postvaccination sera have well correlated with the overall survival of advanced cancer patients who received peptide vaccination Sato et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of the GCAA peptides are reported in Table 2. All these peptides have proven the ability to induce HLA-A02-or HLA-A24-restricted and tumor-speciWc cytotoxic lymphocyte activity in the PBMCs of gastric cancer patients [27,47,51].…”
Section: Reagentsmentioning
confidence: 99%